Sintesis Senyawa Turunan Zerumbon [(1'z, 5'e, 8'e)-4', 4',8'-Trimetil-7'-Oksosikloundeka-1',5',8'-Trien-1'-Il]Metil Propanoat Dengan Pereaksi NatriumPropanoat - Widad, Nurul, Broto Santoso, M.Sc., Apt, Andi Suhendi, M.Sc., Apt (2016)
Zerumbon can be obtained by maceration of dry powder of Zingiberzerumbet with methanol as pelarutnya. Zerumbon do conjugation with the rearrangement of the structure, for example with the addition of bromine, thereby increasing the reactivity of these tersebut. Konjugasizerumbon can increase biological activity (Kitayama et al., 2013) ,Zerumbon have poor solubility in water, so as to increase the solubility of zerumbon to do the synthesis of derivatives zerumbon with various salts. Based (Kitayama et al., 2013) have proven that this salt reagent can increase the solubility of derivatives zerumbon. The synthesis of target molecules involves reacting the starting material zerumbon pendant with sodium propanoat.Sintesis carried out with stirring for 16 jam. Detection results conducted with TLC (Thin Layer Chromatography) with two stationary phase system, solubility test and analysis of 13C NMR and 1H NMR. Synthesized in the form of brownish-yellow liquid with 0.5 mL. Target molecules have a log P of 4.38 with a solubility in water of 1: 100. Target molecule synthesized form a structure consistent with predictions based on the results 13C NMR and 1H NMR are typical of C atoms and protons that are not typical of the compounds contained in the starting material that used.